The gut microbiota and diabetic nephropathy: an observational study review and bidirectional Mendelian randomization study - Han, Yi Zhen; Wang, Yang Zhi Yuan; Zhu, Xing Yu; Du, Bo Xuan; Wang, Yao Xian; Zhang, Xue Qin; Jia, Jia Meng; Liu, Wei Jing; Zheng, Hui Juan (Current controlled trials in cardiovascular medicine, 2025)
Earlier studies have implicated a crucial link between diabetic nephropathy (DN) and the gut microbiota (GM) by considering the gut-kidney axis; however, the specific cause-and-effect connections between these processes remain unclear. To compare changes in the GM between DN patients and control subjects, a review of observational studies was performed. The examination focused on the phylum, family, genus, and species/genus categories. To delve deeper into the cause-effect relationship, instrumental variables for 211 GM taxa (9 phyla, 16 classes, 20 orders, 35 families, and 131 genera), which were eligible for the mbQTL (microbial quantitative trait locus) mapping analysis, were collected from the Genome Wide Association Study (GWAS). A Mendelian randomization investigation was then conducted to gauge their impact on DN susceptibility using data from the European Bioinformatics Institute (EBI) and the FinnGen consortium. The European Bioinformatics Institute data included 1032 DN patients and 451,248 controls, while the FinnGen consortium data consisted of 3283 DN patients and 210,463 controls. Two-sample Mendelian randomization (TSMR) was utilized to determine the link between the GM and DN. The primary method for analysis was the inverse variance weighted (IVW) approach. Moreover, a reverse Mendelian randomization analysis was carried out, and the findings were validated through sensitivity assessments. This review examined 11 observational studies that satisfied the inclusion and exclusion criteria. There was a significant difference in the abundance of 144 GM taxa between DN patients and controls. By employing the MR technique, 13 bacteria were pinpointed as having a causal link to DN (including 3 unknown GM taxa). Even after Bonferroni correction, the protective impact of the phylum Proteobacteria and genus Dialister (Sequeira et al. Nat Microbiol. 5:304-313, 2020; Liu et al. EBioMedicine. 90:104527, 2023) and the harmful impact of the genus Akkermansia, family Verrucomicrobiaceae, order Verrucomicrobia and class Verrucomicrobiae on DN remained significant. No noticeable heterogeneity or horizontal pleiotropy was detected in the instrumental variables (IVs). However, reverse MR investigations have failed to reveal any substantial causal relationship between DN and the GM. Differences in the GM among DN patients and healthy controls are explored in observational studies. We verified the possible connection between certain genetically modified genera and DN, thereby emphasizing the connection between the "gut-kidney" axis and new insights into the GM's role in DN pathogenesis underlying DN. Investigations into this association are necessary, and novel biomarkers for the development of targeted preventive strategies against DN are needed.